2014
DOI: 10.4103/0019-5278.146909
|View full text |Cite
|
Sign up to set email alerts
|

A study of morbidity pattern among iron and steel workers from an industry in central India

Abstract: Background:Iron is the world's most commonly used metal and can usually be found with other elements in the form of steel. In this era of machines, it is the inevitable part in production of various materials like eyeglass frames, jet aircraft, the space shuttle, automobiles, and surgical instruments. Occupational factors make an important contribution to the global burden of disease, but the reliable data on occupational disease are much more difficult to obtain. Hence, the current study was carried out to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…In a case-control study conducted on 400 Indian steel workers in 2014, the overall prevalence of morbidities in the cohort was 60% and the highest morbidity was related to MSDs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study conducted on 400 Indian steel workers in 2014, the overall prevalence of morbidities in the cohort was 60% and the highest morbidity was related to MSDs [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Release of certain gases like coke oven gas, carbon dioxide, tar, benzyl, and carbon monoxide in the steel factory results in several kinds of ailments like discoloration of lips, periodontal diseases, and their long term exposure may lead to carcinoma of lips. [ 7 8 ] Therefore, steel and iron workers are especially prone to occupational health problems and experience more sickness absenteeism, affecting their Oral Health-Related Quality of Life[ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…cross-sectional study conducted by Manish et al, 2014 in an Indian Iron and Steel industry among 400 workers showed that 60% of the workers had occupational morbidities from which 20% had chronic bronchitis and 6% had bronchial asthma.…”
Section: Anothermentioning
confidence: 99%